2017
DOI: 10.3414/me16-02-0014
|View full text |Cite
|
Sign up to set email alerts
|

Can 3D Gamified Simulations Be Valid Vocational Training Tools for Persons with Intellectual Disability?

Abstract: On the basis of this experiment we believe that 3D gamified simulations can be efficient tools to train social and professional skills of persons with intellectual disabilities contributing thus to foster their social inclusion through work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Therefore, the effects of SGs for people with ID regarding each conceptual skill cannot be generalized. The SGs for practical skills are mainly focused on daily living (Burke et al, 2014;Freina et al, 2016) and work-related skills (Chang et al, 2011;Kwon & Lee, 2016;von Barnekow et al, 2017). The SGs are addressed to young adults with ID, and it can be concluded that this target audience is preferred for these sets of skills.…”
Section: Studies Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, the effects of SGs for people with ID regarding each conceptual skill cannot be generalized. The SGs for practical skills are mainly focused on daily living (Burke et al, 2014;Freina et al, 2016) and work-related skills (Chang et al, 2011;Kwon & Lee, 2016;von Barnekow et al, 2017). The SGs are addressed to young adults with ID, and it can be concluded that this target audience is preferred for these sets of skills.…”
Section: Studies Resultsmentioning
confidence: 99%
“…Although in this design phase the end users were not included, a special education professional was involved. A similar approach was followed by von Barnekow et al (2017), in order to design IntegraGame, addressing the appropriate behaviour in a work environment for people with ID.…”
Section: Studies Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The hypothesis of this work, presented by von Barnekow et al [22], is that gamified simulations and serious games can be an effective way of providing this personalized training. Persons with intellectual disability need personalized vocational training to get use to work procedures, be aware of safety protocols and be prepared to handle different situations in the workplace.…”
Section: Can 3d Gamified Simulations Be Valid Vocational Training Toomentioning
confidence: 98%